"And most semely for to be": Julian of Norwich and "The Cloud of Unknowing" on Spiritual Similitude - Harkaway-Krieger, Kerilyn (Journal of medieval religious cultures, 2021)
Both Julian of Norwich and the author of The Cloud of Unknowing use the Middle English term semely to navigate moments of tension surrounding the ability of material signs to convey divine truth. The authors treat a variety of signs, some linguistic, some not, all of which require interpretation to be properly understood. The wide variety of such material signs is captured in the authors' use of the Middle English terms goostly and bodily to identify spiritual and material realities, but also figurative and literal meanings. Seemly signs are suitable, appropriate for the task of communicating spiritual truths. Ultimately, for Julian and the Cloud author, semely identifies a particular relationship between embodied, finite reality, and divine infinitude - while there is no ultimate analogy between these two realities such that material signs are necessary or sufficient to reveal spiritual truths, some material particularities are the "best possible" or "most fitting" way to communicate.